Location Privacy Preservation in Cognitive Radio Networks - Wang, Wei.; Zhang, Qian.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This brief focuses on the current research on location privacy preservation in cognitive radio networks (CRNs). Along with a review of the existing works, this book includes fundamental privacy models, possible frameworks, useful performance, and future research directions. It explores privacy preservation techniques, collaborative spectrum sensing, database-driven CRNS, and modeling potential privacy threats. Conflicts between database owners and unlicensed users can compromise location privacy, and CRNs are a means to mitigate the spectrum scarcity issue due to the increasing demand for wireless channel resources. By examining the current and potential privacy threats, the authors equip readers to understand this developing issue. The brief is designed for researchers and professionals working with computer communication networks and cognitive radio networks. Graduate students interested in networks and communication engineering will also find the brief helpful.
Introduction -- Privacy Preservation Techniques -- Location Privacy Preservation in Collaborative Spectrum Sensing -- Location Privacy Preservation in Database-Driven Cognitive Radio Networks -- Future Research Directions.
Keywords: Computer science; Computer Communication Networks; Telecommunication; Computer Science; Computer Communication Networks; Communications Engineering, Networks